A case report: identifying a novel variant in ELOC(TCEB1)-mutant renal cell carcinoma - Cheng, Hai-Peng; Li, Na-Mei; Zeng, Ke-Xin; Zhou, Peng; Li, Xiao-Hong (Frontiers in Oncology, 2025)
ELOC(TCEB1)-mutant renal cell carcinoma [ELOC(TCEB1)-RCC] is a newly recognized type of RCC characterized by clear cell morphology and ELOC(TCEB1) gene mutation. We analyzed one case with a point mutation in TCEB1 c.218T>A (p.V73E), which is a novel mutation site and has not been reported in ELOC(TCEB1)-RCC. The case involved a male individual of age 48, whose computed tomography scan of the abdomen indicated the presence of a solid nodule located in the kidney. The tumor cells showed expression of PAX8, CA9, AMACR/P504S, Vimentin, CK7, CD10, FH, INI1(SMARCB1) and ELOC(TCEB1), and ELOC was mainly located in the nucleus. CD117, TFE3, HMB45, and SDHB were not express, and the expression rate of Ki67 was <5%. The novel variant in ELOC(TCEB1) gene was identified by the next-generation sequencing (NGS) test, subsequently also confirmed by Sanger sequencing. The ELOC(TCEB1) gene mutation testing is helpful for the diagnosis of this type of RCC. The case further expands our knowledge of the spectrum of TCEB1 gene mutation in ELOC(TCEB1)-RCC and enhances the optimization of clinical decision-making.